Ophiocordyceps furcatosubulata, a new entomopathogenic fungus parasitizing beetle larvae (Coleoptera: Elateridae) - Wang, Yao; Wu, Hui-Juan; Tran, Ngoc Lan; Zhang, Guo-Dong; Souvanhnachit, Sisommay; Wang, Yuan-Bing; Yu, Hong (Phytotaxa, 2021)
A new invertebrate-associated fungus, Ophiocordyceps furcatosubulata, is reported from China, Vietnam and Laos. It is characterized by solitary stromata, clavate and slender stipes, cylindrical fertile parts, furcate and subulate sterile apices, immersed perithecia, short asci, filiform ascospores with multi-septa, short secondary ascospores, hirsutella-like asexual morph with polyphialidic conidiogenous cells, broadly ellipsoid or ellipsoid conidia, and on larvae of elaterid beetles buried in soil. Both morphological observation and phylogenetic analyses of combined nrSSU, nrLSU, tef-1α, rpb1 and rpb2 sequence data support that this fungus is a distinctive species in the genus Ophiocordyceps.